Management and outcomes of cochlear implantation in patients with congenital cytomegalovirus (cCMV)-related deafness. (4th July 2017) - Hoey, Andrew Wesley; Pai, Irumee; Driver, Sandra; Connor, Steve; Wraige, Elizabeth; Jiang, Dan
Abstract : Objective: Congenital Cytomegalovirus (cCMV) is a well-defined cause for neonatal mortality and morbidity, particularly sensorineural hearing loss and other neurodevelopmental disruption. We present a retrospective study which provides an overview of the assessment and preoperative work-up for patients diagnosed with cCMV and their cochlear implant (CI) outcomes. Method: This was a retrospective case series study of all children with a confirmed diagnosis of cCMV who underwent cochlear implantation at St Thomas' Hospital from 2003 to 2015. Data were collected on the preoperative audiology, imaging findings, and neurological assessment. CI outcomes were measured using the Speech Intelligibility Rating (SIR), Category of Auditory Performance (CAP), and Infant-Toddler Meaningful Auditory Integration Scale (IT-MAIS). Results: Eleven patients underwent cochlear implantation, 45% had severe-to-profound hearing loss, and 55% had bilateral profound hearing loss. The mean age at initial assessment was 2.1 years (median 1.7, range 0.6–7.5) and the mean age of implantation was 4.0 years (median 2.5, range 0.9–11.8). The mean length of follow-up was 4.8 years (median 2.3, range 1.5–14). Six patients had bilateral simultaneous implantation (55%), four bilateral sequential (36%), and one unilateral (9%). Nine patients had white matter changes on magnetic resonance imaging, largely in the periventricular and cortical regions. Of the 11 patients, 4 (36%) had associated neurological comorbidities and 3 (27%) had additional neurocognitive developmental delay of varying severity. The majority of patients showed improvement in auditory outcomes. No statistically significant correlation was found between age of implantation, neurocognitive, and neurological comorbidities or length of follow-up and hearing outcomes. Conclusion: While the overall outcomes were mixed, most children in our cohort were found to benefit from cochlear implantation. Our data also highlight the significant neurodevelopmental comorbidities associated with cCMV and their negative impact on CI outcomes. With the recent advances in medical treatment, this underlines the importance of multidisciplinary management of these patients.